KONTRIBUSI TEORI DISKURSUS TERHADAP STUDI POLITIK - DAMANIK, AHMAD TAUFAN (Politeia: Jurnal Ilmu Politik, 2012)
Discourse theory is a social theory that developed rapidly since the 1980s. Itâs influential to po-litical science. This study describes discourse theory as an approach, especially in social re-search. This study explored the contribution of discourse analysis approach in the study of politics, as the advantages. Collecting data of this study is using library research. The analysis using descriptive analysis techniques. This study found that there are important argumentations which explain that the discourse analysis is useful for the study of politics. First, the diversity in selecting issues and research questions; Second, discourse analysis can explain social phenom-ena evidently; Third, research findings always contested, disassembled, transformed and changed; Fourth, the ability to generalize is possible in the case studies or qualitative research and even able to provide an explanation as a result of quantitative research; Fifth, discourse analysis is also possible to construct theories or otherwise to perform the falsification theories.Keywords: Discourse theory, political science, analysis techniques.